Functional cooperation of of IL-1β and RGS4 in the brachial plexus avulsion mediated brain reorganization - Li, Jifeng; Zhao, Hui; Luo, Pengbo; Gu, Yudong (Journal of Brachial Plexus and Peripheral Nerve Injury, 2010)
Backgrounds There is considerable evidence that central nervous system is continuously modulated by activity, behavior and skill acquisition. This study is to examine the reorganization in cortical and subcortical regions in response to brachial plexus avulsion.Methods Adult C57BL/6 mice were divided into four groups: control, 1, 3 and 6 month of brachial plexus avulsion. IL-1β, IL-6 and RGS4 expression in cortex, brainstem and spinal cord were detected by BiostarM-140 s microarray and real-time PCR. RGS4 subcellular distribution and modulation were further analyzed by primary neuron culture and Western Blot.Results After 1, 3 and 6 months of brachial plexus avulsion, 49 (0 up, 49 down), 29 (17 up, 12 down), 13 (9 up, 4 down) genes in cerebral cortex, 40 (8 up, 32 down), 11 (7 up, 4 down), 137 (63 up, 74 down) in brainstem, 27 (14 up, 13 down), 33 (18 up, 15 down), 60 (29 up, 31 down) in spinal cord were identified. Among the regulated gene, IL-1β and IL-6 were sustainable enhanced in brain stem, while PKACβ and RGS4 were up-regulated throughout cerebral cortex, brainstem and spinal cord in 3 and 6 month of nerve injury. Intriguingly, subcellular distribution of RGS4 in above three regions was dependent on the functional correlation of PKA and IL-1β.Conclusion Data herein indicated that brachial plexus avulsion could efficiently initiate and perpetuate the brain reorganization. Network involved IL-1β and RGS4 signaling might implicate in the re-establish and strengthening of the local circuits at the cortical and subcortical levels.